Cerebral Dominance for Language in Literates and Illiterates - PJ, Kumar (Journal of All India Institute of Speech and Hearing)
Cameron, Currier and Haerer (1971) studied 65 patients who had left hemisphere damage in order to see whether there existed a relationship between literacy and language disturbances in these patients. They reported more language disturbances in literates and semi-literates than with the illiterates. Seventy eight per cent of their literate group and sixty four per cent of their semiliterate group exhibited language disturbances with the left hemisphere damage. Only thirty six per cent of their illiterate group had language disturbances.